PROGRAM ASSERTIVENES TRAINING DAN PROGRAM PSIKO EDUKASI KELUARGA SEBAGAI MODEL DALAM PREVENSI ADIKSI GAME ONLINE PADA REMAJA DI KOTA PADANG - Renidayati .; Suhaimi . (Poltekkes Kemenkes Padang, 2018)
Excessive use of online games in adolescents can lead to addiction. Online game addiction is associated with limited time of rest, insomnia, sleep deprivation, academic decline, decreased self-esteem, and decreased life satisfaction with everyday life. Through Assertive Training Program and Psycho-educational Program in Families are expected to improve the ability of self-esteem, assertiveness and knowledge of teenagers to prevent the Online Game Addiction. The study design